2018
DOI: 10.3389/fpsyt.2017.00307
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of “Attachment-Based Compassion Therapy” in the Treatment of Fibromyalgia: A Randomized Controlled Trial

Abstract: ObjectiveThere is a growing interest in evaluating the effectiveness of compassion interventions for treating psychological disorders. The present study evaluated the effectiveness of “attachment-based compassion therapy” (ABCT) in the treatment of fibromyalgia (FM), and the role of psychological flexibility as a mediator of improvements.MethodsA total of 42 patients with FM were randomly assigned to ABCT or relaxation (active control group). Both the intervention and control condition were combined with treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 44 publications
1
55
1
1
Order By: Relevance
“…However, the efficiency of ABCT as a FM treatment has not been previously analyzed. In this study, we extend the results of Montero-Marin et al [15] by examining the 3-month cost-utility of ABCT compared to Relaxation in terms of gains in QALYs from a healthcare perspective. ABCT and Relaxation were structurally equivalent, which provides a comparison of ABCT to a suitable active control that matches it in non-specific factors, but does not contain compassionand mindfulness-based components.…”
Section: Why It Is Important To Know the Cost-utility Of Abctmentioning
confidence: 64%
See 2 more Smart Citations
“…However, the efficiency of ABCT as a FM treatment has not been previously analyzed. In this study, we extend the results of Montero-Marin et al [15] by examining the 3-month cost-utility of ABCT compared to Relaxation in terms of gains in QALYs from a healthcare perspective. ABCT and Relaxation were structurally equivalent, which provides a comparison of ABCT to a suitable active control that matches it in non-specific factors, but does not contain compassionand mindfulness-based components.…”
Section: Why It Is Important To Know the Cost-utility Of Abctmentioning
confidence: 64%
“…The same meta-analysis showed that compared to active control conditions, there was a significant moderate effect size for improvements in self-compassion (d = 0.60), mindfulness (d = 0.46), depression (d = 0.62), anxiety (d = 0.42), psychological distress (d = 0.40), and well-being (d = 0.48). Furthermore, Montero-Marin and colleagues [15] showed that ABCT as a coadjuvant of usual care produced greater improvements in the functional status of patients with fibromyalgia (FM) compared to relaxation practices at post-treatment (d = 1.33) and 3-month follow-up (d = 1.38). Significant improvements in the ABCT group were also observed in the following secondary outcomes at post-treatment and follow-up: clinical severity (d = 0.96 and d = 1.14), anxiety (d = 1.03 and d = 0.90), depression (d = 0.94 and d = 1.01), quality of life (d = 0.84 and d = 0.85), and psychological flexibility (d = 1.13 and d = 1.18).…”
Section: Loving-kindness Meditation and Compassion-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a randomised controlled trial comparing self-compassion training with waitlist control for adults with diabetes found significant improvements in mental health and metabolic outcomes among the intervention group [26]. In addition, a randomised controlled trial of self-compassion training compared with an active control (relaxation) reported a 40% absolute risk reduction for health status in the intervention group for patients with fibromyalgia [43]. Further, previous work has found that self-compassion interventions improve mental health and wellbeing among healthy adolescents [8,9,28].…”
Section: Intervention Approach and Theoretical Basismentioning
confidence: 99%
“…Similarly, higher PF has also been found to be associated with less pain intensity and interference, less anxiety and depressive symptomatology, and improved physical and mental functioning in patients with FM [17,23,24]. Furthermore, PF (and its individual components) have also been reported to mediate clinical changes in acceptance-and mindfulness-based interventions delivered to patients with chronic pain [22,25] and FM [26][27][28].…”
Section: Introductionmentioning
confidence: 91%